Evaluation of the Effect of Ultra-Processed Food (UPF) Consumption of Cardiometabolic Risk in Professional Nigerian Adults: A Quantitative Study - Edem , Asukwo Asukwo; Marc , Chrysanthou; Mgbang , John Edward; Inyang , Aniekeme N‎disa (International Journal of Basic and Applied Sciences, 2025)
Background and objectives: to evaluate the effect of ultra-processed food (UPF) consumption on cardio-metabolic risk in professional Nigerian adults.Methods: Using standard methods, frequency, prevalence, and health implications of UPF consumption of ‎respondents were determined. A cross-sectional study design was adopted, with a simple random sampling ‎method in selecting 250 participants from five faculties in the College of Medical Sciences, University of ‎Calabar, Nigeria. Data were collected using a structured web-based questionnaire, collated using Microsoft Excel ‎software, and analysed using a combination of Chi-square (X2) test, one-sample t-test, and Pearson’s correlation ‎analysis using SPSS software.‎Findings: The overall frequency of UPF intake was relatively low, with a significant (P
Keywords: Blood Pressure; Body Mass Index; Cardio-Metabolic Risk; Food Choice; Ultra-Processed Foods